Improvement of osteogenic differentiation potential of placenta-derived mesenchymal stem cells by metformin via AMPK pathway activation - Sirikul Manochantr; Ladda Meesuk; Nuengruethai Chadee; Jintamai Suwanprateeb; Chairat Tantrawatpan; Pakpoom Kheolamai (Stem Cell Research & Therapy)
Abstract Background Placenta-derived human mesenchymal stem cells (PL-MSCs) have gained a lot of attention in the field of regenerative medicine due to their availability and bone-forming capacity. However, the osteogenic differentiation capacity of these cells remains inconsistent and could be improved to achieve greater efficiency. Although metformin, a widely used oral hypoglycemic agent, has been shown to increase bone formation in various cell types, its effect on osteogenic differentiation of PL-MSCs has not yet been investigated. Therefore, the objective of this study was to examine the effect of metformin on the osteogenic differentiation capacity of PL-MSCs and the underlying mechanisms. Methods The PL-MSCs were treated with 0.5 to 640 µM metformin and their osteogenic differentiation capacity was examined by an alkaline phosphatase (ALP) activity assay, Alizarin red S staining and expression levels of osteogenic genes. The role of adenosine 5′-monophosphate-activated protein kinase (AMPK) signaling in mediating the effect of metformin on the osteogenic differentiation capacity of PL-MSCs was also investigated by determining levels of phosphorylated AMPK (pAMPK)/AMPK ratio and by using compound C, an AMPK inhibitor. Results The results showed that 10–160 µM metformin significantly increased the viability of PL-MSCs in a dose- and time-dependent manner. Furthermore, 80–320 µM metformin also increased ALP activity, matrix mineralization, and expression levels of osteogenic genes, runt-related transcription factor 2 (RUNX2), osterix (OSX), osteocalcin (OCN) and collagen I (COL1), in PL-MSCs. Metformin increases osteogenic differentiation of PL-MSCs, at least in part, through the AMPK signaling pathway, since the administration of compound C inhibited its enhancing effects on ALP activity, matrix mineralization, and osteogenic gene expression of PL-MSCs. Conclusions This study demonstrated that metformin at concentrations of 80–320 μM significantly enhanced osteogenic differentiation of PL-MSCs in a dose- and time-dependent manner, primarily through activation of the AMPK signaling pathway. This finding suggests that metformin could be used with other conventional drugs to induce bone regeneration in various bone diseases. Additionally, this study provides valuable insights for future osteoporosis treatment by highlighting the potential of modulating the AMPK pathway to improve bone regeneration.